All‐Copper Nanocluster Based Down‐Conversion White Light‐Emitting Devices. Issue 11 (21st June 2016) - Wang, Zhenguang; Chen, Bingkun; Susha, Andrei S.; Wang, Weihua; Reckmeier, Claas J.; Chen, Rui; Zhong, Haizheng; Rogach, Andrey L.
Abstract : Most of the present‐day down‐conversion white light‐emitting devices (WLEDs) utilize rare‐earth elements, which are expensive and facing the problem of shortage in supply. WLEDs based on the combination of orange and blue emitting copper nanoclusters are introduced, which are easy to produce and low in cost. Orange emitting Cu nanoclusters (NCs) are synthesized using glutathione as both the reduction agent and stabilizer, followed by solvent induced aggregation leading to the emission enhancement. Photoluminescence quantum yields (PL QY) of 24% and 43% in solution and solid state are achieved, respectively. Blue emitting Cu nanoclusters are synthesized by reduction of polyvinylpyrrolidone supported Cu(II) ions using ascorbic acid, followed by surface treatment with sodium citrate which improves both the emission intensity and stability of the clusters, resulting in the PL QY of 14% both in solution and solid state. All‐copper nanocluster based down‐conversion WLEDs are fabricated by integrating powdered orange and blue emitting Cu NC samples on a commercial GaN LED chip providing 370 nm excitation. They show favorable white light characteristics with Commission Internationale de l'Eclairage color coordinates, color rendering index, and correlated color temperature of (0.36, 0.31), 92, and 4163 K, respectively. Abstract : Photoluminescence of blue and orange emitting Cu nanoclusters (NCs) is enhanced by surface treatment with sodium citrate and the solvent induced aggregation, respectively, resulting in high quantum yields of 14% and 43% in the solid state. White light emitting diodes are fabricated using powdered Cu NCs as phosphors, with a high color rendering index of 92 and low correlated color temperature of 4163 K.